2011
DOI: 10.1089/gtmb.2011.0027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison ofKRASMutation Tests in Colorectal Cancer Patients

Abstract: The KRAS pathway and studies evaluating KRAS as a prognostic marker in colorectal cancer are discussed along with advances in KRAS gene mutation testing. Highly sensitive real-time polymerase chain reaction (PCR) methods were developed for this purpose. We examined the applicability of direct sequencing and two real-time PCR methods in the diagnosis of KRAS mutations. We used real-time PCR and direct sequencing-based methods to determine applicability of these KRAS mutation tests in 64 colorectal cancers. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…EntroGen provides a commercially available real‐time PCR kit for KRAS and BRAF mutation detection, which uses allele‐specific primers without employing a pre‐amplification step. For the EntroGen assay, 50 ng gDNA from tissues was amplified with gene specific primers and the KRAS codons 12, 13 and 61 and BRAF V600E mutations were detected using allele‐specific probes (EntroGen), as described previously . For CTC samples, a nested PCR was first performed on 10 ng gDNA extracted from CellSearch‐enriched CTCs, followed by a second PCR with the allele‐specific probes as described before …”
Section: Methodsmentioning
confidence: 99%
“…EntroGen provides a commercially available real‐time PCR kit for KRAS and BRAF mutation detection, which uses allele‐specific primers without employing a pre‐amplification step. For the EntroGen assay, 50 ng gDNA from tissues was amplified with gene specific primers and the KRAS codons 12, 13 and 61 and BRAF V600E mutations were detected using allele‐specific probes (EntroGen), as described previously . For CTC samples, a nested PCR was first performed on 10 ng gDNA extracted from CellSearch‐enriched CTCs, followed by a second PCR with the allele‐specific probes as described before …”
Section: Methodsmentioning
confidence: 99%
“…In fact, in a recent review of 578 cases referred to our laboratory, we found that 528 (91.3%) specimens contained more than 30% of neoplastic cells 61. Besides the percentage of neoplastic cells, the limit of detection (LOD) of this technique partly depends on the specific mutation and on the experience of the person interpreting the data 62. When a KRAS mutation is identified by direct sequencing, both mutant and wild-type alleles are seen on the sequencing electropherograms.…”
Section: The Methodsmentioning
confidence: 99%
“…However, this assay requires a minimum of 30-50% tumor cells to successfully detect a mutation. 2, 10, 15, 19 Other methods in use, such as pyrosequencing or high resolution melt analysis, have higher sensitivities and require lower percentages of malignant DNA to successfully detect a mutation. 4, 9, 20 Nonetheless, all methods, by definition, have a limit of analytic sensitivity which represents the minimum percentage of tumor cells in a tissue sample required to correctly identify a mutation.…”
Section: Introductionmentioning
confidence: 99%
“…4, 9, 20 Nonetheless, all methods, by definition, have a limit of analytic sensitivity which represents the minimum percentage of tumor cells in a tissue sample required to correctly identify a mutation. 10 …”
Section: Introductionmentioning
confidence: 99%